The marine palaemonid shrimps (Crustacea, Deapoda, Caridea) of the Dutch Caribbean - Fransen, Charles H.j.m. (Zootaxa, 2023)
Species of the decapod family Palaemonidae are common components of tropical coastal waters and coral reefs. The majority of these species are symbionts of various invertebrate phyla. Despite a long history of research on their species diversity in the Dutch Caribbean, recent field expeditions have yielded much new information. Combined with examinations of specimens housed in Naturalis Biodiversity Center and information from literature, a comprehensive list of Dutch Carribean palaemonids is provided. Newly collected material was primarily identified via morphological analyses. Additional molecular phylogenetic analyses based on mitochondrial COI and 16S and nuclear Histone 3 (H3) genes were conducted in search of cryptic species on the one hand and to check conspecifity in species that were found on multiple host species on the other hand. In total, 46 species are here listed for the Dutch Caribbean of which 24 are here recorded for the first time for one of the islands. One species new to science was discovered and is herein described. Sixty new host associations are recorded. In light of biodiversity loss and increasing anthropogenic pressure on declining coral reefs, documenting the diversity of palaemonids and other coral reef species to provide baseline data takes on a new urgency.